COMMUNITY SERVICE PROGRAM: THE EFFECTIVENESS OF STRESS MANAGEMENT TRAINING ON REDUCING STRESS, DEPRESSION AND ANXIETY LEVELS AMONG SENIOR HIGH SCHOOL STUDENTS - Fikri; Bahril Hidayat Lubis; Cutra Aslinda; Mohd Radzi Tarmizi A Halim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Purpose: This study aims to assess the impact of stress management training using SEFT module on reducing stress, anxiety and depression among high school students State Senior High School One in Kuantan Mudik Kuansing. Design: This study employed a quasi-experimental study, specifically the One-Group Pretest-Posttest Design. Method: This study involved 30 high school students experiencing stress and anxiety who lack coping mechanisms. Utilizing the Depression Anxiety Stress Scale (DASS), data was collected during a community service project. Prior to the intervention, participants completed a pre-test using the DASS Scale. Following this, students received stress management psychoeducation and SEFT therapy (Spiritual Emotional Freedom Technique), after which a post-test was administered. Findings: The analysis revealed no significant differences in mean scores between pre- and post-intervention assessments on the stress, anxiety, and depression scales. Significances: This study suggests the implementation of a more intensive stress management program for school adolescents.